Membranous nephropathy: Clearer pathology and mechanisms identify potential strategies for treatment - Chung, Edmund Y. M.; Wang, Yuan M.; Keung, Karen; Hu, Min; McCarthy, Hugh; Wong, Germaine; Kairaitis, Lukas; Bose, Bhadran; Harris, David C. H.; Alexander, Stephen I. (Frontiers in Immunology, 2022)
Primary membranous nephropathy (PMN) is one of the common causes of adult-onset nephrotic syndrome and is characterized by autoantibodies against podocyte antigens causing in situ immune complex deposition. Much of our understanding of the disease mechanisms underpinning this kidney-limited autoimmune disease originally came from studies of Heymann nephritis, a rat model of PMN, where autoantibodies against megalin produced a similar disease phenotype though megalin is not implicated in human disease. In PMN, the major target antigen was identified to be M-type phospholipase A2 receptor 1 (PLA2R) in 2009. Further utilization of mass spectrometry on immunoprecipitated glomerular extracts and laser microdissected glomeruli has allowed the rapid discovery of other antigens (thrombospondin type-1 domain-containing protein 7A, neural epidermal growth factor-like 1 protein, semaphorin 3B, protocadherin 7, high temperature requirement A serine peptidase 1, netrin G1) targeted by autoantibodies in PMN. Despite these major advances in our understanding of the pathophysiology of PMN, treatments remain non-specific, often ineffective, or toxic. In this review, we summarize our current understanding of the immune mechanisms driving PMN from animal models and clinical studies, and the implications on the development of future targeted therapeutic strategies.